Risk Factors Related To Pesticide Exposure In Banjar Horticultural Farmers - Dewa Ayu Eka Wahyuni; I Made Muliarta; Susy Purnawati (Eduvest - Journal of Universal Studies, 2022)
Agriculture in Indonesia is the driving force for the country's economy. Farmers in an effort to improve the quality and productivity of agricultural products use pesticides. The use of pesticides to control pests is growing rapidly. Banjar farmers from the Dasong Department are active pesticide users, so there is a potential for pesticide exposure. This study aims to determine the relationship between risk factors and complaints on horticultural farmers in Banjar Dinas Dasong, Pancasari Village, Sukasada District, Buleleng Regency. This study is an analytical observational study with a cross-sectional approach using 46 respondents. Data were analyzed by SPSS using chi-square test and logistic regression. The results of the Chi-Square test showed that there was no significant relationship between age, pesticide dose, duration of spraying, time of spraying, and frequency of spraying with complaints from farmers (p>0.05). While there is a significant relationship between the use of PPE with complaints to farmers (p <0.05). The results of the logistic regression test showed that the duration of spraying, spraying time, frequency of spraying, and use of PPE with complaints to farmers was not significant (p>0.05). This is due to other external factors. This research can be concluded that there is no correlation between the duration of spraying, spraying time, frequency of spraying, and the use of PPE with the complaints of farmers in Banjar Dinas Dasong, Pancasari Village, Sukasada District, Buleleng Regency.